Best in Session Award - Zopiatis, Anastasios (My University, 2026)
2017 Las Vegas Global Conference on Business and Finance (GCBF), 2nd – 5th of January 2017, Las Vegas, Nevada. Recipient of the Best in Session Award
Keywords: Business and industry